2019
DOI: 10.1016/j.ejca.2018.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Intense dose-dense epirubicin, paclitaxel, cyclophosphamide versus weekly paclitaxel, liposomal doxorubicin (plus carboplatin in triple-negative breast cancer) for neoadjuvant treatment of high-risk early breast cancer (GeparOcto—GBG 84): A randomised phase III trial

Abstract: Background: GeparOcto compared efficacy and safety of two chemotherapy regimens in high-risk early breast cancer (BC): sequential treatment with intense dose-dense epirubicin, paclitaxel, and cyclophosphamide (iddEPC) and weekly treatment with paclitaxel plus non-pegylated liposomal doxorubicin (M, Myocetâ) with additional carboplatin (PM(Cb)) in triple-negative BC (TNBC). Patients and methods: Patients with cT1c-cT4a-d and centrally assessed human epidermal growth factor receptor (HER)2-positive BC or TNBC we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(79 citation statements)
references
References 32 publications
(38 reference statements)
2
76
0
1
Order By: Relevance
“…Speci c AEs such as decreased appetite, vomiting, rash, and diarrhea, which were consistent with the studies of Krop [57] et al In grade 3 and higher AEs, there was no signi cant increase in the overall incidence of AEs, and diarrhea was the only signi cant increase in the speci c AEs. This conclusion was consistent with the study results of Schneeweiss [58] et al We speculated that diarrhea might be related to gastric epidermal cells expressing HER2 [59]. Studies have shown that for elderly patients who are more prone to dehydration, continuous grade 1-2 diarrhea may be debilitating [60], which prompts us to pay more attention to the association between AEs.…”
Section: Discussionsupporting
confidence: 90%
“…Speci c AEs such as decreased appetite, vomiting, rash, and diarrhea, which were consistent with the studies of Krop [57] et al In grade 3 and higher AEs, there was no signi cant increase in the overall incidence of AEs, and diarrhea was the only signi cant increase in the speci c AEs. This conclusion was consistent with the study results of Schneeweiss [58] et al We speculated that diarrhea might be related to gastric epidermal cells expressing HER2 [59]. Studies have shown that for elderly patients who are more prone to dehydration, continuous grade 1-2 diarrhea may be debilitating [60], which prompts us to pay more attention to the association between AEs.…”
Section: Discussionsupporting
confidence: 90%
“…These results are strongly in line with recently published excellent outcome after 18 weeks of docetaxel/carbo backbone without anthracycline use. 20 Although improved pCR under NACT suggests platinumcontaining CHT 12,23,30 as a promising treatment strategy in early TNBC, survival benefits are not yet established 17,18 ; moreover, optimal therapy combinations, 13,14,16 particularly deescalated approaches and predictive markers have yet to be determined. The present translational analysis of the WSG-ADAPT-TN trial has sought to address this need to select patients for deescalated regimens.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Replacement of standard weekly solvent-based paclitaxel by nab-paclitaxel (nab-pac), 15 increased dosage of alkylating agents 16 or addition of carboplatin (carbo) to A/T containing NACT 10,17 have led to increased pCR rates (49-60%), albeit with higher toxicity. Such approaches may improve survival in TNBC, [16][17][18] but evidence is not yet conclusive. Remarkably, although BRCA1 mutation-frequently associated with TNBC-is highly predictive for efficacy of carbo as a monotherapy agent, 19 no predictive effect on survival regarding carbo addition has been demonstrated so far in the context of polychemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Ob die Hinzunahme von Platin auch im Rahmen eines dosisdichten/ dosisintensivierten Regimes prognostische Vorteile für die TNBC-Patientinnen bringt, ist derzeit unklar. In der neoadjuvanten GeparOcto-Studie [70] wurden TNBC-Patientinnen entweder mit einer dosisdichten Platin-haltigen Therapie in Kombination mit Anthrazyklinen und Taxanen oder mit dem dosisdichten/ dosisintensivierten ETC-Regime behandelt. Für die TNBC-Patientinnen zeigte sich keine höhere pCR für das Platin-haltige Regime bei insgesamt günstigerem Nebenwirkungsspektrum unter platinfreier Behandlung.…”
Section: Hinzunahme Von Carboplatin?unclassified